Non-Linear Buckling Analysis of Axially Loaded Column with Non-Prismatic I-Section - Adrian Pramudita Dharma; Bambang Suryoatmono (Journal of the Civil Engineering Forum, 2019)
In order to use material efficiently, non-prismatic column sections are frequently employed. Tapered-web column cross-sections are commonly used, and design guides of such sections are available. In this study, various web-and-flange-tapered column sections were analysed numerically using finite element method to obtain each buckling load assuming the material as elastic-perfectly plastic material. For each non-prismatic column, the analysis was also performed assuming the column is prismatic using average cross-section with the same length and boundary conditions. Buckling load of the prismatic columns were obtained using equation provided by AISC 360-16. This study proposes a multiplier that can be applied to the buckling load of a prismatic column with an average cross-section to acquire the buckling load of the corresponding non-prismatic column. The multiplier proposed in this study depends on three variables, namely the depth tapered ratio, width tapered ratio, and slenderness ratio of the prismatic section. The equation that uses those three variables to obtain the multiplier is obtained using regression of the finite element results with a coefficient of determination of 0.96.